2007
DOI: 10.1095/biolreprod.107.060004
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidase-Inactivated tACE Action In Vivo: Selective Inhibition of Sperm-Zona Pellucida Binding in the Mouse1

Abstract: The angiotensin-converting enzyme (ACE) plays a crucial role in male fertilization and is a key regulator of blood pressure. Testicular ACE (tACE), the germinal specific isozyme expressed on different promoters, exclusively carries out the role of ACE in fertility, although the site and mode of action are not well known. To investigate the contribution of tACE in fertilization, we produced transgenic mouse lines carrying a dipeptidase-inactivated mutant. Although the transgenic mice showed normal blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The male germ-cell-specific variant (tACE) controls ADAM3 distribution on the membrane (6). The GPIase activity of tACE (i.e., the release of glycosylphosphatidylinositol-anchored proteins from the membrane) is implicated in ADAM3 modification during epididymal maturation (32). In addition to tissue-specific factors, recent studies indicated that the ubiquitously expressed proteins, TPST2 (protein-tyrosine sulfotransferase 2) and INPP5B (inositol polyphosphate-5-phosphatase B), are involved in ADAM3 quality control (13,33).…”
Section: Discussionmentioning
confidence: 99%
“…The male germ-cell-specific variant (tACE) controls ADAM3 distribution on the membrane (6). The GPIase activity of tACE (i.e., the release of glycosylphosphatidylinositol-anchored proteins from the membrane) is implicated in ADAM3 modification during epididymal maturation (32). In addition to tissue-specific factors, recent studies indicated that the ubiquitously expressed proteins, TPST2 (protein-tyrosine sulfotransferase 2) and INPP5B (inositol polyphosphate-5-phosphatase B), are involved in ADAM3 quality control (13,33).…”
Section: Discussionmentioning
confidence: 99%
“…Fuchs and colleagues reported that dipeptidase activity of testicular ACE (tACE) is required for sperm-ZP binding (Fuchs et al, 2005). Thereafter, we reported that dipeptidase activity of tACE is functional in the epididymis (Deguchi et al, 2007). In addition, Shum and co-workers have shown that angiotensin II, a product of ACE dipeptidase action, regulates the distribution of proton channels in the epididymal epithelium and contributes to the pH homeostasis of the epididymal fluids (Shum et al, 2008).…”
Section: Egfp(k268q)-gpi Release and Gm1 Relocation Is Associated Wmentioning
confidence: 92%
“…ACE sheds various GPI-anchored proteins from the sperm surface such as TESP5 [ID: T1-175] and , and this function plays a role in fertilization (Kondoh et al, 2005). Transgenic mice carrying a mutant dipeptidase-inactivated tACE are fertile, but sperm-zona pellucida binding is impaired (Deguchi et al, 2007).…”
Section: Flagellar Proteins and Abnormalities Associatedmentioning
confidence: 99%